O papel do leitor na recepção de K. relato de uma busca, de Bernardo Kucinski: preenchimento de lacunas e atualização do texto - Pott, Airton (2020)
K.: relato de uma busca, the book; Bernardo Kucinski, the author; Skoob, the social network where some readers expressed themselves. These are the members of the corpora of our studies regarding the reception of a contemporary book, first published in 2011, but which gained relevance in 2014, when it was published by a better known publisher. Taking as its narrative theme the story of a father searching for his missing daughter during the military dictatorship, K.: relato de uma busca keeps in his pages many revealing information, including based on real facts. There is much in this Kucinski book to be identified by its readers, and this is what we intend to ascertain through comments from Skoob Internet users about K.: relato de uma busca. We anchor our studies on the theories of reception by Jauss (1979, 1994), and literary hermeneutics, synthesized by Zilberman (1989), and on the aesthetic effect of Iser (1996a, 1996b, 1999a, 1999b). We also visited concepts related to the theory of mediations, especially by Martín-Barbero (1997), as it addresses concepts that we consider fundamental to our research and are, in a way related, to the aesthetics of reception. However, in the analysis chapter, we have scaled Gagnebin (2006), Seligmann-Silva (2000) and Figueiredo (2017) to help us understand words that are history oriented, since it is not the scope of reception aesthetics to address them. Because it is a book related to the military dictatorship, historical period, these scholars help us to understand even some terms used by the users of Skoob, recipients of the book K.: relato de uma busca. Concepts, words and statements such as forgetfulness, memory, memories, absence, trauma, and many other terms that help in retracting and recalling events related to the suffering of victims of a period such as the military dictatorship help readers express their readings and understandings. About a book like K.: relato de uma busca report of a search. However, countless concepts of reception theories, aesthetic effect and cultural mediations are also essential inputs for the analysis of comments recorded in the Skoob network about Kucinski's book. Given the fact that each reader has his or her own cultural background, it is natural for each reader to emphasize different aspects of the book in question, as happened with comments about K.: relato de uma busca. Therefore, we separated the comments or part of them regarding the features that caught our attention and stood out in terms of quantity and emphatic approach. There was a certain unanimity on the part of readers participating in the Skoob network, recipients of K.: relato de uma busca, regarding the reading of Kucinski's work, highlighting positive aspects about it. In fact, many of the Internet users surprised us with their comments, emphasizing with dexterity and knowledge about the book, the author, and even when making comparisons with other authors, works and historical periods.